Effects of N addition on soil exchangeable cations in a young Keteleeria fortunei var. cyclolepis forest. Issue 3 (3rd July 2019) - Wang, Yong; Huang, Xinhao; Jiang, Yi; Liu, Xiongsheng; Zhu, Fan
ABSTRACT: The effects of simulated nitrogen (N) addition on soil exchangeable cations were assessed in a young Keteleeria fortunei var. cyclolepis forest in subtropical China. Three N addition schemes with three replications were designed for the forest control (without N addition, CK), low N (5 g N m −2 a −1, L-N) and high N (50 g N m −2 a −1, H-N). Results showed that continuous N addition resulted in increased, although not statistically significant, plant biomass of K. fortunei var. cyclolepis, while it significantly decreased cation exchange capacity (CEC), base saturation (BS) and exchangeable base cations (BCs) (especially Ca 2+ and Mg 2+ under high N addition). General soil properties (except total P) were significantly affected by high N addition compared with the control. High N addition significantly increased the concentration of foliar N, and decreased the concentrations of foliar P, Ca 2+ and Mg 2+ . Soil pH was also significantly altered by increased N addition, indicating that N addition significantly accelerated soil acidification. This study found that N addition was negatively correlated with soil pH, CEC and Ca 2+, and that loss of BCs might be related to increased NO3 – .